2020
DOI: 10.18502/jnfs.v5i2.2800
|View full text |Cite
|
Sign up to set email alerts
|

Demographics Factors Associated with Housewives' Attitude towards Transgenic Food Products in Yazd

Abstract: Background: In the last two decades, genetic engineering has led to the production of genetically modified or transgenic products in the world using the modern biotechnology. However, accepting such products by consumers is still in doubt with respect to their negative effects on the environment and human health. Thus, the present study aimed to evaluate the attitude of housewives in Yazd towards transgenic food products. Methods: This cross-sectional descriptive study was conducted on 500 housewives in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition, the women reported that they receive information about genetically modified food products through television and radio [23]. Norwegian women are more skeptical of GM crops than men, and older people need more discounts to buy GM products, which means that older consumers are less receptive to GM products than younger people [24], and public trust in government and belief in science is increased by positive media influence and increases in public support [25]. Moreover, in order to improve the effectiveness of food policies, policymakers should invest in advertising labels and target the elderly and people with a lower education levels [26].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the women reported that they receive information about genetically modified food products through television and radio [23]. Norwegian women are more skeptical of GM crops than men, and older people need more discounts to buy GM products, which means that older consumers are less receptive to GM products than younger people [24], and public trust in government and belief in science is increased by positive media influence and increases in public support [25]. Moreover, in order to improve the effectiveness of food policies, policymakers should invest in advertising labels and target the elderly and people with a lower education levels [26].…”
Section: Introductionmentioning
confidence: 99%